ANALISIS KINERJA KEUANGAN BERDASARKAN RASIO PROFITABILITAS PADA USAHA SHOES CARE CLINIC DI SAMARINDA PERIODE 2016 â€“ 2017 - Nurrahim, Adi - (EKONOMIA, 2019)
2018. The purpose of this research is to analyze financial performance of Shoes Care Clinic business in Samarinda based on profitability ratio. Â Â Â Â Â Â This research uses the theoretical basis of financial management theory regarding financial performance analysis based on profitability ratios. Analytical tools used in this study Net Profit Margin, Return on Investment and Return on Equity. Â Â Â Â Â Â Based on the results of analysis and discussion, the financial performance ofÂ Shoes Care Clinic business decreased from 2016 to 2017. Net Profit Margin in 2016 was 0,22% decreased in 2017 to 0.1651%. Return On Investment in 2016 was 0,3357% decreased in 2017 to 0,1926% and Return on Equity in 2016 was 0,3546 decreased in 2017 to 0,2006%. Â Â Â Â Â Â The results of this study indicate that the Shoes Care Clinic business has not been efficient in managing its capital due to increased business costs and reduced operating revenues. Thus with this the hypothesis that researcher stated earlier is:â€The financial performance of Shoes Care Clinic business Samarinda has decreased in terms of profitability ratio from 2016 to 2017â€ was accepted. This is because results of analysisÂ from 2016 to 2017 decreased.